Art Communication in the Dongkrek Performance of Madiun - Renda, Rapi; Mawardi, Taufik; Biagi, I Wayan Kusuma Di (Gema Cendekia Institute, 2024)
Artistic communication can be defined as the process of exchanging information, ideas, and expressions through the medium of art. In the context of performance, artistic communication not only involves the interaction between artists and the audience but also encompasses the ways in which cultural values and traditions are conveyed and understood. In relation to this perspective, this research aims to elucidate the patterns and processes of artistic communication in the Dongkrek performance in Madiun. The objective of this study is to analyse and delve into the artistic communication within the Dongkrek performance in Madiun. Specifically, this research aims to identify the elements of communication present in the performance. The method employed in this study is a qualitative approach, with data collection techniques including observation, interviews, and documentation studies. Observations were conducted during the Dongkrek performance to understand the dynamics of communication occurring between the artists and the audience. Dongkrek in Madiun functions not only as entertainment but also as an important medium for cultural communication. Dongkrek, which is part of the local performing arts tradition, conveys the social, cultural, and identity values of the Madiun community. Through the analysis of various elements in the performance, including music, dance, and narrative, it was found that Dongkrek possesses the ability to convey profound messages to its audience.